2018
DOI: 10.24820/ark.5550190.p010.783
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the conformation of C-linked α-D-mannopyranosides and their application toward the synthesis of low nanomolar E. coli FimH ligands

Abstract: C-Allyl -D-mannopyranosides were prepared via a variety of routes to determine an optimal route to the anomers. The relative conformational energies of the key intermediate was evaluated by molecular modeling which showed the conventional 4 C1 chair conformation to be the lowest energy conformer. This finding was also confirmed by NMR and X-ray crystallography. The perbenzoylated C-allyl mannoside was also converted into 1,1'-biphenyl analogues using a palladium-catalyzed Heck reaction. Two of the resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…Analogues of O - and C -linked α-D-mannopyranosides with hydrophobic and aryl substituents have already been identified as potent E. coli FimH antagonists having low nanomolar Kds or IC 50 s [5,10,18,21,22]. Para -substituted biphenyl derivatives were shown to be particularly appealing owing to their numerous favorable binding interactions within the identified tyrosine gate formed between Tyr48 and Tyr137 [18,21,23,24,25]. In turn, some derivatives were shown to bind better when the Tyr-gate is either open, half-open, or close, further pointing toward rationally design glycol therapeutics [20,22,26,27,28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analogues of O - and C -linked α-D-mannopyranosides with hydrophobic and aryl substituents have already been identified as potent E. coli FimH antagonists having low nanomolar Kds or IC 50 s [5,10,18,21,22]. Para -substituted biphenyl derivatives were shown to be particularly appealing owing to their numerous favorable binding interactions within the identified tyrosine gate formed between Tyr48 and Tyr137 [18,21,23,24,25]. In turn, some derivatives were shown to bind better when the Tyr-gate is either open, half-open, or close, further pointing toward rationally design glycol therapeutics [20,22,26,27,28].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to its O - and C -linked congeners, we chose the S -allyl α-D-mannopyranoside 9 as key starting materials. However, rather than using a palladium catalyzed Heck reaction and a series of aryl iodides for the cross-coupling as before [18,21], we decided to extend its alkenyl functionality by a metathesis reaction using 4-vinyl-1,1′-biphenyl ( 10 ) and Grubbs 2 nd generation catalyst. This alternative strategy was considered equally appealing owing to its potential to access a diversified library of analogs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, several aryl C -mannopyranosides carrying alkenyl aglycons were shown as promising candidates with excellent binding affinities against E. coli FimH [ 40 , 41 ]. However, their poor water solubility has restricted their further development as drug candidates.…”
Section: Resultsmentioning
confidence: 99%
“…Amid the various α-D-mannopyranoside inhibitors described thus far, C -linked glycomimetics residues harboring hydrophobic aglycons are still considered worthy candidates as potent FimH inhibitors. Several of these synthetic candidates showed improved binding affinities and increased hydrolytic stability [ 30 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%